Bare battery cell, preparation method and application thereof
By designing the phase change heat absorption layer and flame retardant layer on the negative electrode sheet of the battery cell, the problems of thermal runaway and ablation of the battery cell are solved, and the safety performance and thermal management capabilities of the battery cell are significantly improved, and high energy density and long cycle life are maintained.
Patent Information
- Application Number
- CN202411974351.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
Existing battery cells are prone to thermal runaway due to excessive internal temperature, which may cause ablation of the battery body after thermal runaway, increasing the risk of shell corrosion or internal shortness. The existing flame retardant solution will increase the cost of Mylar auxiliary materials.
A bare electric cell is designed, and its surface negative electrode sheet includes a phase change heat-absorbing layer and a flame retardant layer stacked in sequence. The phase change heat-absorbing layer is composed of polyethylene glycol, acrylic acid and carboxymethyl cellulose. The flame retardant layer is composed of polyethylene, polyamide and organic phosphorus-based flame retardant. Through these layers, heat is absorbed and stored to prevent the flame from spreading.
Effectively reduce the internal temperature of the battery cell, prevent thermal runaway, significantly enhance the safety performance and thermal management capabilities of the battery cell, broaden the scope of application of the battery cell under extreme temperature conditions, while maintaining high energy density and long cycle life.
Smart Images

Figure CN119786688A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a bare battery cell, a preparation method thereof, and applications thereof. Background Art
[0002] With the development of high-nickel ternary lithium batteries and large-capacity lithium iron phosphate batteries, the safety risks of battery cells are increasing, especially the increasing number of problems caused by thermal runaway, such as passive valve opening, smoke, fire, and even explosion. Currently, the main solutions to the problem of thermal runaway of battery cells focus on two aspects: one is to reduce the heat generation and short-circuit Joule heating of the battery cell chemical system; the other is to enhance the heat dissipation capacity of the battery cell. However, without affecting the electrical performance and mechanical strength of the battery cell, the space for improving the thermal safety margin in these two directions is relatively limited and cannot fully meet the needs of reducing heat accumulation in the battery cell system. Therefore, it is particularly urgent to explore new methods to reduce system heat accumulation.
[0003] The industry is increasingly focusing on the design of heat-absorbing materials inside and outside the battery cell, and the use of the phase change reaction of the material at high temperature to absorb heat to reduce the heat accumulation of the system. At present, there are two main solutions for using phase change heat absorption of materials to improve thermal safety performance. One is to add heat-absorbing rubber pads to the module and pack (battery pack), and place the heat-absorbing rubber pads between the battery cells to reduce the temperature inside the battery pack, which shows good results in controlling heat spread. However, this method can only reduce the risk of heat spread failure in the battery pack, and cannot solve the thermal runaway problem of the battery cell itself. The other is to introduce phase change heat absorption inside the battery cell to reduce the heat accumulation of the battery cell level system, but the technology currently under development in the industry is to mix heat-absorbing material particles in the diaphragm or wrap a layer of phase change heat-absorbing wrapping film on the outer surface of the bare battery cell. However, this solution has a loss in electrical performance and energy density, and there are major obstacles to introducing mass production, making it difficult to commercialize.
[0004] In addition, when an internal short circuit occurs in the battery cell, causing the local temperature to be too high, local ablation points are likely to occur, burning the Mylar layer (polyester film layer) on the outside of the bare battery cell, and there is a risk of contact between the negative electrode and the shell, which may lead to corrosion and leakage of the shell during later use. After leakage, the battery cell is at risk of arcing and fire in the battery pack. If the ablation point is located at the position of the pole ear, there is also the risk of internal short contact between the positive pole ear and the negative pole, which will further aggravate the thermal runaway of the battery cell. At present, the solution to the flame retardant problem of bare cells is to apply a flame retardant layer on the Mylar layer on the outside of the bare cell, but this solution will increase the cost of Mylar auxiliary materials. It is worth noting that square and cylindrical cells are usually wrapped with Mylar protective film, while soft-pack cells are not wrapped with Mylar protective film, so the flame retardant effect of soft-pack cells is relatively poor. Summary of the Invention
[0005] The main purpose of the present invention is to provide a bare battery cell, a preparation method and application thereof, so as to solve the problem in the prior art that the battery cell is prone to thermal runaway due to excessively high internal temperature, and thermal runaway is prone to cause battery cell body ablation.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a bare battery cell, which is placed inside a shell. The bare battery cell includes a surface negative electrode sheet, and the side of the shell facing the surface negative electrode sheet is the shell surface. In the direction away from the shell surface, the surface negative electrode sheet includes a coating, a current collector and a negative electrode membrane stacked in sequence; in the direction away from the shell surface, the coating includes a flame retardant layer and a phase change heat absorption layer stacked in sequence. The coating design of the present application makes full use of the space where the outer graphite does not participate in the electrochemical reaction, and adopts a double coating of phase change heat absorption layer-flame retardant layer to replace the outer graphite membrane, which can effectively avoid the impact on the volume energy density and electrical performance of the battery cell, while significantly enhancing the safety performance of the battery cell. This design is conducive to improving the overall safety and reliability of the battery cell, especially in terms of thermal management, and can significantly broaden the scope of application of the battery cell under extreme temperature conditions.
[0007] Furthermore, the phase-change heat absorption layer comprises polyethylene glycol, acrylic acid, and carboxymethyl cellulose. Preferably, the weight ratio of polyethylene glycol to carboxymethyl cellulose is (0.6-4.5):1; and / or the weight ratio of acrylic acid to carboxymethyl cellulose is (0.05-0.35):1. The inventors precisely controlled the composition of the phase-change heat absorption layer within this range, enabling the coating to store heat energy through a solid-state phase change at high temperatures and release it at low temperatures, thereby more effectively improving the heat absorption performance and stability of the battery cell.
[0008] Furthermore, the phase-change heat absorption layer comprises, by weight percentage, 30-80% polyethylene glycol, 1-20% acrylic acid, and 10-50% carboxymethyl cellulose. This phase-change heat absorption layer not only provides more efficient thermal management but also maintains good coating adhesion, further improving both high- and low-temperature performance of the battery.
[0009] Furthermore, the material of the flame retardant layer includes polyethylene, polyamide, and an organophosphorus flame retardant; preferably, the oxygen content in the polyamide is ≥10wt%; preferably, the organophosphorus flame retardant includes one or more of phosphate esters, phosphites, and organophosphorus salts, more preferably, the phosphate ester includes one or more of trichloroethyl phosphate, dimethyl methylphosphonate, and triphenyl phosphate; more preferably, the phosphite includes one or more of methyl phosphite, triethyl phosphite, and tri(propylene glycol) phosphite; more preferably, the organophosphorus salt includes one or more of aluminum phosphate, lanthanum phosphate, and ammonium polyphosphate. The present application achieves not only efficient flame retardant protection but also cost-effectiveness by precisely controlling the composition of the flame retardant layer.
[0010] Furthermore, the flame-retardant layer comprises polyethylene and an organophosphorus flame retardant in a weight ratio of (1-1.8):1; and / or polyamide and an organophosphorus flame retardant in a weight ratio of (0.5-0.9):1. This flame-retardant layer, comprising these components, more effectively prevents flame spread during thermal runaway, thereby further improving battery safety.
[0011] Furthermore, the flame-retardant layer comprises, by weight, 36-60% polyethylene, preferably 40-45%; and / or 5-40% polyamide, preferably 18-25%; and / or 20-40% organophosphorus flame retardant, preferably 30-40%. Under these conditions, the flame-retardant layer can effectively maintain lightweight while providing more adequate flame-retardant protection, further improving battery safety.
[0012] Furthermore, the coating has a thickness of 40 to 500 μm; preferably, the phase change heat absorption layer has a thickness of 30 to 400 μm; and / or the flame retardant layer has a thickness of 10 to 100 μm. Under these conditions, the coating can not only more fully absorb the heat of the battery in an overheated state, ensuring good thermal response and heat absorption efficiency, and providing more comprehensive flame retardant protection, but also does not excessively increase the overall thickness and weight of the bare battery cell, further improving the overall performance of the battery, allowing it to maintain high energy density and long cycle life while meeting safety requirements.
[0013] According to another aspect of the present invention, a method for preparing the above-mentioned bare cell is provided, wherein the bare cell comprises a surface negative electrode sheet, with the side of the shell facing the surface negative electrode sheet being the shell surface, and in a direction away from the shell surface, the surface negative electrode sheet comprises a coating, a current collector, and a negative electrode film stacked in sequence; in a direction away from the shell surface, the coating comprises a flame retardant layer and a phase change heat absorption layer stacked in sequence; the current collector comprises a first surface and a second surface, and the preparation method comprises the following steps: step S1, applying a raw material for the phase change heat absorption layer to the first surface of the current collector to obtain a phase change heat absorption layer; step S2, applying a raw material for the flame retardant layer to the surface of the phase change heat absorption layer to obtain a flame retardant layer; step S3, applying a raw material for the negative electrode film to the second surface of the current collector to obtain a surface negative electrode sheet; step S4, using the surface negative electrode sheet as the outermost sheet to prepare the bare cell. The preparation method of the present application is simple and efficient, capable of large-scale production of batteries with excellent thermal management and flame retardant properties, and is suitable for industrial production of battery manufacturing.
[0014] Furthermore, the coating density of the phase change heat absorption layer raw material is 0.5-5 mg / cm 2 ; and / or, the coating density of the flame retardant layer material is 0.1 to 1.5 mg / cm 2This application can further optimize the performance of the coating by controlling the combination mode and coating density, ensuring a rapid response when the battery overheats, while providing sufficient flame retardant protection in the event of thermal runaway, making it suitable for the use of batteries in various extreme environments.
[0015] According to another aspect of the present invention, a secondary battery is provided, comprising the above-mentioned bare cell. Due to its unique thermal management and flame-retardant design, the bare cell of the present application not only significantly improves the safety performance of the battery, but also maintains the battery's high energy density and long cycle life, making it suitable for battery applications in electric vehicles, energy storage systems, portable electronic devices, aerospace, and various extreme environments.
[0016] By applying the technical solution of the present invention, a phase change heat absorption layer and a flame retardant layer are sequentially provided on the surface negative electrode sheet of the bare battery cell of the present invention, which can not only effectively absorb and store excess heat generated by internal chemical reactions at the battery cell body level, reduce the internal temperature of the battery cell, and prevent the occurrence of thermal runaway, but also form an effective barrier under high temperature conditions, inhibit the spread of flames, and significantly enhance the thermal safety performance of the battery cell and its battery pack. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings, which constitute part of this application, are intended to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are intended to explain the present invention and do not constitute an undue limitation of the present invention. In the accompanying drawings:
[0018] Figure 1 A schematic structural diagram of a bare cell according to embodiment 1 of the present invention is shown;
[0019] Figure 2 The figure shows the structure of the surface negative electrode sheet of Example 1 of the present invention;
[0020] Figure 3 The figure shows the structure of the surface negative electrode sheet of comparative example 1 of the present invention.
[0021] The above drawings include the following reference numerals:
[0022] 1. Surface negative electrode sheet; 2. Inner positive electrode sheet; 3. Inner negative electrode sheet; 4. Separator; 5. Negative electrode membrane; 6. Current collector; 7. Phase change heat absorption layer; 8. Flame retardant layer. DETAILED DESCRIPTION
[0023] It should be noted that, in the absence of conflict, the embodiments and features of the embodiments in this application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0024] As described in the background of the present invention, there are problems in the prior art that the battery cell is prone to thermal runaway due to excessively high internal temperature, and the battery cell body is easily ablated after thermal runaway. Specifically, the internal temperature of the battery cell is too high due to heat generation and short-circuit Joule heat during thermal runaway, and the resulting risk of thermal runaway of the battery cell body; the Mylar protective film of the bare battery cell is ablated due to excessively high local temperature of the internal short circuit, resulting in shell corrosion or greater internal short risk, as well as the risk of arcing and fire. In order to solve the above problems, in a typical embodiment of the present invention, a bare battery cell is provided, which is placed inside the shell, and the bare battery cell includes a surface negative electrode plate, with the side of the shell facing the surface negative electrode plate as the shell surface, and in the direction away from the shell surface, the surface negative electrode plate includes a coating, a current collector and a negative electrode film stacked in sequence; in the direction away from the shell surface, the coating includes a flame retardant layer and a phase change heat absorption layer stacked in sequence.
[0025] It should be noted that the negative electrode membrane in this application refers to the negative electrode active material layer, which is understandable to those skilled in the art and will not be elaborated here.
[0026] A typical bare cell structure is as follows Figure 1 As shown, it includes a negative electrode sheet, a separator and a positive electrode sheet stacked in sequence. For ease of understanding, this application divides the negative electrode sheet into a surface negative electrode sheet and an inner negative electrode sheet.
[0027] In existing bare battery cells, the graphite diaphragm on the outer surface of the outermost electrode usually does not exert its capacity. This application is the first to combine a phase change heat absorption layer and a flame retardant layer double coating on the outer surface of the outermost electrode of the bare battery cell to replace the existing graphite diaphragm layer.
[0028] Among them, the phase change heat absorption layer absorbs heat and undergoes a solid-solid phase change at a higher temperature (such as ≥60°C), which can absorb and store a large amount of heat, effectively reducing heat accumulation, inhibiting the occurrence of thermal runaway, and helping to improve the thermal stability of the battery in high-temperature environments. When the battery cell temperature is at a lower temperature (such as ≤10°C), the phase change coating undergoes a solid-solid phase change again, releasing heat and heating the battery cell, improving the battery cell's dynamics and charge-discharge performance under low-temperature conditions and optimizing the battery cell's temperature management.
[0029] This application adds a flame-retardant layer outside the phase-change heat absorption layer to enhance the safety of the battery cell. The flame-retardant layer decomposes under heat, forming a dense layer that effectively isolates heat and oxygen, preventing the combustion of organic matter within the battery cell, reducing heat generation, and preventing the spread of flames. This effectively reduces the risk of internal short circuits within the battery cell, localized overheating leading to corrosion of the shell or greater internal short circuits caused by the burning of the Mylar layer, thereby improving the overall safety and reliability of the battery cell. This design not only helps improve the flame-retardant performance of the battery cell, but also avoids the use of the more expensive Mylar flame-retardant layer, thus balancing the economic benefits and safety of the battery.
[0030] It should be noted that in the prior art, a double coating of a phase change heat absorption layer and a flame retardant layer is usually not provided on the surface of the electrode. This is because the current mass-produced battery cells usually have a small capacity and can basically meet the thermal safety requirements. However, with the application of high-nickel, large-capacity ternary or energy storage battery cells greater than 340Ah, the safety window has narrowed, and new technologies need to be developed to effectively improve the safety window of the battery, promote the advancement of battery technology and the sustainable development of the energy industry. The coating design of this application makes full use of the space where the outer graphite does not participate in the electrochemical reaction, and adopts a double coating of a phase change heat absorption layer and a flame retardant layer to replace the outer graphite membrane, which can effectively avoid the impact on the volume energy density and electrical properties of the battery cell, while significantly enhancing the safety performance of the battery cell. This design is conducive to improving the overall safety and reliability of the battery cell, especially in terms of thermal management, and can significantly broaden the scope of application of the battery cell under extreme temperature conditions.
[0031] In a preferred embodiment, the material of the phase change heat absorption layer includes polyethylene glycol, acrylic acid and carboxymethyl cellulose; preferably, the weight average molecular weight of polyethylene glycol is 3000-10000 g / mol; preferably, in the material of the phase change heat absorption layer, the weight ratio of polyethylene glycol and carboxymethyl cellulose is (0.6-4.5):1; and / or, the weight ratio of acrylic acid and carboxymethyl cellulose is (0.05-0.35):1. In this ratio, polyethylene glycol is the main phase change material, and its molecular weight and content directly affect the phase change temperature and heat storage capacity; acrylic acid and CMC work together to more effectively improve the adhesion and stability of the phase change heat absorption layer. The inventors precisely control the composition of the phase change heat absorption layer within the above range, and the coating can store heat energy in a solid phase change at high temperature and release it at low temperature, thereby more effectively improving the heat absorption performance and stability of the battery cell.
[0032] If the polyethylene glycol content is too high, the acrylic acid or carboxymethyl cellulose content may be relatively low, affecting the adhesion of the coating to the current collector. If the polyethylene glycol content is too low, the heat absorption effect of the heat absorption layer may be reduced. If the acrylic acid content is too high, the dispersion of the mixed slurry may be reduced. If the acrylic acid content is too low, the adhesion may be poor. If the carboxymethyl cellulose content is too high, the mixed slurry may agglomerate, which is not conducive to processing. If the carboxymethyl cellulose content is too low, the adhesion may be poor. In a preferred embodiment, the phase change heat absorption layer material comprises 30-80% polyethylene glycol, 1-20% acrylic acid, and 10-50% carboxymethyl cellulose, based on weight percentage. The phase change heat absorption layer with the above composition ratio can not only provide more efficient thermal management, but also maintain good coating adhesion, which can further improve the high and low temperature performance of the battery.
[0033] In a preferred embodiment, the material of the flame retardant layer includes polyethylene, polyamide and an organophosphorus flame retardant; preferably, the oxygen content in the polyamide is ≥10wt%, more preferably 15-30wt%; preferably, the organophosphorus flame retardant includes one or more of phosphate esters, phosphites and organophosphorus salts, more preferably, the phosphate ester includes one or more of trichloroethyl phosphate, dimethyl methylphosphonate and triphenyl phosphate; more preferably, the phosphite includes one or more of methyl phosphite, triethyl phosphite and tri(propylene glycol) phosphite; more preferably, the organophosphorus salt includes one or more of aluminum phosphate, lanthanum phosphate and ammonium polyphosphate.
[0034] When the battery cell is exposed to abnormally high temperatures, these organophosphorus flame retardants decompose more rapidly, releasing phosphoric acid, which transforms the polyamide into a uniform, dense carbonized layer. This dense carbon layer not only significantly reduces the conduction of flame heat, effectively preventing further diffusion of combustion heat into the battery cell, but its structural density also significantly reduces oxygen penetration, thereby inhibiting oxidation reactions within the cell and reducing the critical element required for combustion. Simultaneously, the released phosphoric acid, acting as a chemical flame retardant, directly acts on organic matter within the cell, preventing it from fully burning. This significantly reduces heat generation and mitigates the possibility of thermal runaway under high-temperature conditions.
[0035] The dual protection mechanism of carbon barrier and phosphoric acid fire extinguishing not only significantly improves the safety of battery cells under high-temperature conditions, but also effectively improves the long-term effectiveness and stability of the flame retardant effect by inhibiting the premature decomposition of the flame retardant. This application achieves not only efficient flame retardant protection but also cost-effectiveness by precisely controlling the composition of the flame retardant layer.
[0036] To further enhance the flame retardancy, in a preferred embodiment, the flame retardant layer comprises a polyethylene to organophosphorus flame retardant ratio of 1 to 1.8:1 by weight, and / or a polyamide to organophosphorus flame retardant ratio of 0.5 to 0.9:1 by weight. This combination of ingredients effectively prevents flame spread during thermal runaway, further enhancing battery safety.
[0037] In a preferred embodiment, the flame-retardant layer comprises, by weight, 36-60% polyethylene, preferably 40-50%; and / or 5-40% polyamide, preferably 18-25%; and / or 20-40% organophosphorus flame retardant, preferably 30-40%. Under these conditions, the flame-retardant layer can effectively maintain lightweight while providing more comprehensive flame-retardant protection, further improving battery safety.
[0038] To further provide thermal management and flame retardant protection while ensuring battery energy density, in a preferred embodiment, the coating has a thickness of 40 to 500 μm; preferably, the phase change heat absorption layer has a thickness of 30 to 400 μm; and / or the flame retardant layer has a thickness of 10 to 100 μm. Under these conditions, the coating can not only more fully absorb the heat of the battery in an overheated state, ensuring good thermal response and heat absorption efficiency, and providing more sufficient flame retardant protection, but also will not excessively increase the overall thickness and weight of the bare battery cell, further improving the overall performance of the battery, allowing it to maintain high energy density and long cycle life while meeting safety requirements.
[0039] In a preferred embodiment, the current collector comprises one or more of copper foil, aluminum foil, and a composite current collector; and / or the negative electrode film layer comprises one or more of a graphite layer, silicon carbon, and silicon oxide; and / or the phase change temperature of the phase change heat absorption layer is 10 to 60°C. The coating of the present application can quickly respond to overheating of the battery, absorbing heat, thereby more effectively suppressing the spread of flames and improving the safety performance of the battery.
[0040] In another typical embodiment of the present invention, a method for preparing the above-mentioned bare cell is also provided. The bare cell includes a surface negative electrode sheet, with the side of the shell facing the surface negative electrode sheet as the shell surface. In the direction away from the shell surface, the surface negative electrode sheet includes a coating, a current collector, and a negative electrode film stacked in sequence; in the direction away from the shell surface, the coating includes a flame retardant layer and a phase change heat absorption layer stacked in sequence; the current collector includes a first surface and a second surface. The preparation method includes the following steps: step S1, applying a raw material for the phase change heat absorption layer to the first surface of the current collector to obtain a phase change heat absorption layer; step S2, applying a raw material for the flame retardant layer to the surface of the phase change heat absorption layer to obtain a flame retardant layer; step S3, applying a raw material for the negative electrode film to the second surface of the current collector to obtain a surface negative electrode sheet. In this process, common preparation methods, such as hot pressing or cold pressing, can be used to ensure good contact between the negative electrode film and the current collector. Step S4, using the surface negative electrode sheet as the outermost sheet, to prepare the bare cell. The bare cell can be prepared by winding or lamination. The preparation method of the present application is simple and efficient, capable of large-scale production of batteries with excellent thermal management and flame retardancy, and is suitable for industrial production of battery manufacturing.
[0041] In a preferred embodiment, the coating is selected from brush coating, spin coating or spray coating; and / or the coating density of the phase change heat absorption layer raw material is 0.5 to 5 mg / cm 2 ; and / or, the coating density of the flame retardant layer material is 0.1 to 1.5 mg / cm 2This application can further optimize the performance of the coating by controlling the combination mode and coating density, ensuring a rapid response when the battery overheats, while providing sufficient flame retardant protection in the event of thermal runaway, making it suitable for the use of batteries in various extreme environments.
[0042] In another typical embodiment of the present invention, a secondary battery is also provided, comprising the above-mentioned bare cell. Due to its unique thermal management and flame retardant design, the bare cell of the present application can not only significantly improve the safety performance of the battery, but also maintain the high energy density and long cycle life of the battery, and is suitable for battery applications in electric vehicles, energy storage systems, portable electronic devices, aerospace, and various extreme environments. It should be noted that the cells of the present application include but are not limited to soft-pack cells, square cells, and cylindrical cells.
[0043] The present application is further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in this application.
[0044] Example 1
[0045] Step S1: The phase change heat absorption layer material comprises, by weight percentage, 50% polyethylene glycol (PEG, weight-average molecular weight 5000 g / mol), 10% acrylic acid (AA), and 40% carboxymethyl cellulose (CMC). In a ternary soft-pack battery cell with a thickness of 15 mm, a length of 359 mm, a width of 113 mm, and a capacity of 101 Ah, the phase change heat absorption layer material is evenly coated on the first surface of the current collector 6 (copper foil). The coating density of the phase change heat absorption layer material is controlled to 3 mg / cm 2 The obtained phase change heat absorption layer 7 has a thickness of 120 μm.
[0046] In step S2, the flame retardant layer material includes 50% polyethylene (PE), 18% polyamide (the oxygen content in the polyamide is 20 wt%), and 32% trimethyl phosphate, an organic phosphorus flame retardant, according to weight percentage. The flame retardant layer material is continuously coated on the phase change heat absorption layer, and the coating density of the flame retardant layer material is controlled to be 1 mg / cm 2 The thickness of the obtained flame retardant layer 8 is 20 μm.
[0047] Step S3 , combining the second surface of the current collector with the negative electrode material (graphite), forming a negative electrode film 5 on the second surface of the current collector, and obtaining a surface negative electrode sheet 1 .
[0048] Step S4, using the surface negative electrode sheet as the outermost layer, assemble the surface negative electrode sheet with the positive electrode sheet (made of iron lithium, i.e., the inner positive electrode sheet 2 of the present application), the negative electrode sheet (made of graphite, i.e., the inner negative electrode sheet 3 of the present application), and the separator 4 through a winding or lamination process, wherein the flame retardant layer of the surface negative electrode sheet faces outward toward the shell, and the other side is connected to the phase change heat absorption layer, and the side of the surface negative electrode sheet coated with the negative electrode material faces inward toward the positive electrode sheet to prepare a bare cell. The obtained bare cell is assembled with the electrolyte and the shell to obtain a finished cell.
[0049] The structural diagram of the bare cell is shown in Figure 1 , the schematic diagram of the structure of the surface negative electrode is shown in Figure 2 .
[0050] Example 2
[0051] The only difference from Example 1 is:
[0052] In step S1, the phase change heat absorption layer material comprises, by weight percentage, 50% polyethylene glycol (PEG, weight-average molecular weight 5000 g / mol), 10% acrylic acid (AA), and 40% carboxymethyl cellulose (CMC). In a 97Ah lithium iron phosphate blade cell with a thickness of 27 mm, a length of 285 mm, a width of 97 mm, the phase change heat absorption layer material is evenly applied to one surface of the current collector (copper foil). The coating density of the phase change heat absorption layer material is controlled to 3 mg / cm 2 , the thickness of the phase change heat absorption layer is 120μm.
[0053] In step S2, the flame retardant layer material comprises, by weight percentage, 50% polyethylene (PE), 18% polyamide (the oxygen content in the polyamide is 15 wt%), and 32% trimethyl phosphate, an organic phosphorus flame retardant. The flame retardant layer material is then coated on the phase change heat absorption layer, with the coating density of the flame retardant layer material set to 1 mg / cm 2 , the thickness of the flame retardant layer is 20μm.
[0054] Example 3
[0055] The only difference from Example 1 is:
[0056] Step S1, according to weight percentage, the raw materials of the phase change heat absorption layer include 70% polyethylene glycol (PEG, weight average molecular weight of 5000g / mol), 10% acrylic acid (AA) and 20% carboxymethyl cellulose (CMC).
[0057] Example 4
[0058] The only difference from Example 1 is:
[0059] Step S1, according to weight percentage, the raw materials of the phase change heat absorption layer include 40% polyethylene glycol (PEG, weight average molecular weight of 5000g / mol), 15% acrylic acid (AA) and 45% carboxymethyl cellulose (CMC).
[0060] Example 5
[0061] The only difference from Example 1 is:
[0062] Step S1, according to weight percentage, the raw materials of the phase change heat absorption layer include 30% polyethylene glycol (PEG, weight average molecular weight of 5000 g / mol), 20% acrylic acid (AA) and 50% carboxymethyl cellulose (CMC).
[0063] Example 6
[0064] The only difference from Example 1 is:
[0065] Step S1, according to weight percentage, the raw materials of the phase change heat absorption layer include 80% polyethylene glycol (PEG, weight average molecular weight of 5000 g / mol), 1% acrylic acid (AA) and 19% carboxymethyl cellulose (CMC).
[0066] Example 7
[0067] The only difference from Example 1 is:
[0068] Step S2, according to weight percentage, the flame retardant layer raw materials include 40% polyethylene (PE), 20% polyamide (the oxygen content in polyamide is 15wt%) and 40% organic phosphorus flame retardant triphenyl phosphate.
[0069] Example 8
[0070] The only difference from Example 1 is:
[0071] In step S2, the flame retardant layer material comprises, by weight percentage, 45% polyethylene (PE), 25% polyamide (the oxygen content in the polyamide is 15 wt%), and 30% triphenyl phosphate, an organic phosphorus flame retardant.
[0072] Example 9
[0073] The only difference from Example 1 is:
[0074] Step S1: evenly apply the phase change heat absorption layer material on the first surface of the current collector (copper foil), and control the coating density of the phase change heat absorption layer material to be 4 mg / cm 2 , the thickness of the phase change heat absorption layer is 160μm.
[0075] Step S2: Continue coating the flame retardant layer material on the phase change heat absorption layer, and control the coating density of the flame retardant layer material to be set to 1.5 mg / cm 2 , the thickness of the flame retardant layer is 30μm.
[0076] Example 10
[0077] The only difference from Example 1 is:
[0078] Step S1: evenly apply the phase change heat absorption layer material on the first surface of the current collector (copper foil), and control the coating density of the phase change heat absorption layer material to be 0.5 mg / cm 2 , the thickness of the phase change heat absorption layer is 30μm.
[0079] Step S2: Continue coating the flame retardant layer material on the phase change heat absorption layer, and control the coating density of the flame retardant layer material to be set to 1.5 mg / cm 2 , the thickness of the flame retardant layer is 100μm.
[0080] Example 11
[0081] The only difference from Example 1 is:
[0082] Step S1: evenly apply the phase change heat absorption layer material on the first surface of the current collector (copper foil), and control the coating density of the phase change heat absorption layer material to be 5 mg / cm 2 , the thickness of the phase change heat absorption layer is 400μm.
[0083] Step S2: Continue coating the flame retardant layer material on the phase change heat absorption layer, and control the coating density of the flame retardant layer material to be set to 0.1 mg / cm 2 , the thickness of the flame retardant layer is 10μm.
[0084] Example 12
[0085] The only difference from Example 1 is:
[0086] Step S1 : evenly coating the raw material of the phase change heat absorption layer on the first surface of the current collector (copper foil), and controlling the thickness of the phase change heat absorption layer to be 30 μm.
[0087] Step S2: Continue coating the flame retardant layer material on the phase change heat absorption layer, and control the thickness of the flame retardant layer to be 10 μm.
[0088] Example 13
[0089] The only difference from Example 1 is:
[0090] Step S1 : evenly coating the raw material of the phase change heat absorption layer on the first surface of the current collector (copper foil), and controlling the thickness of the phase change heat absorption layer to be 400 μm.
[0091] Step S2: Continue coating the flame retardant layer material on the phase change heat absorption layer, and control the thickness of the flame retardant layer to be 100 μm.
[0092] Comparative Example 1
[0093] The only difference from Example 1 is:
[0094] A graphite film layer is used to replace the coating layer including the phase change heat absorption layer and the flame retardant layer in the surface negative electrode plate of Example 1.
[0095] The schematic diagram of the structure of the surface negative electrode is shown in Figure 3 In the accompanying drawings, 5 represents the negative electrode membrane and 6 represents the current collector.
[0096] Comparative Example 2
[0097] The only difference from Example 2 is that:
[0098] Graphite material is used to replace the coating including the phase change heat absorption layer and the flame retardant layer in the surface negative electrode plate of Example 2.
[0099] Comparative Example 3
[0100] The only difference from Example 1 is:
[0101] In the surface negative electrode sheet, the coating does not include a phase change heat absorption layer.
[0102] Comparative Example 4
[0103] The only difference from Example 1 is:
[0104] In the surface negative electrode sheet, the coating does not include a flame retardant layer.
[0105] Comparative Example 5
[0106] The only difference from Example 1 is:
[0107] In the coating of the surface negative electrode sheet, the order of the phase change heat absorption layer and the flame retardant layer was swapped.
[0108] The performance test results of the battery cells prepared in the above examples and comparative examples are shown in Table 1.
[0109] Test method:
[0110] ARC T1 test: The test is carried out under adiabatic conditions, starting from 40℃, and stopping heating and keeping warm for 1 hour every time the temperature rises by 5℃, entering the search phase. When dT / dt>0.02℃ / min and remains stable, the temperature is T1 temperature, and the heating power is 300KW.
[0111] Hot box test: Start from 40℃, heat up at a rate of 5℃ / min to 130℃, keep warm for 30min, then continue heating at 5℃ / min until thermal runaway occurs.
[0112] Thermal creep test: Four identical cells are stacked together to form a small module. The second cell is subjected to a 55°C, 1mΩ short-circuit test to induce thermal runaway. The time difference between adjacent cells in the module experiencing thermal runaway is observed.
[0113] Table 1
[0114]
[0115]
[0116] As can be seen from the above, compared with the comparative examples, the embodiments of the present invention significantly improve the thermal safety stability of the battery cell and significantly enhance the thermal safety window of the battery cell and battery pack by adopting a phase change heat-absorbing and flame-retardant double-layer design for the outermost electrode cell. At the same time, the phase change heat-absorbing coating can release heat to heat the battery cell at low temperatures, further improving the battery cell dynamics and increasing the low-temperature cycle and rate performance of the battery cell. In addition, this solution utilizes the outermost graphite negative electrode thickness space where the capacity is not utilized for the heat-absorbing and flame-retardant double-layer coating, which does not occupy the thickness space of the battery cell and does not lose the battery cell volume energy density.
[0117] In addition, it can be seen that when the various process parameters are within the preferred range of the present invention, the electrochemical performance, cycle performance and safety performance of the battery are even better.
[0118] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A bare battery cell, placed inside a housing, characterized in that: The bare cell comprises a surface negative electrode sheet, and a side of the outer shell facing the surface negative electrode sheet is the outer shell surface. In the direction away from the outer shell surface, the surface negative electrode sheet includes a coating, a current collector and a negative electrode membrane stacked in sequence; In the direction away from the outer shell surface, the coating includes a flame retardant layer and a phase change heat absorption layer stacked in sequence.
2. The bare battery cell according to claim 1, characterized in that: The material of the phase-change heat-absorbing layer includes polyethylene glycol, acrylic acid and carboxymethyl cellulose; Preferably, in the material of the phase change heat absorption layer, the weight ratio of the polyethylene glycol to the carboxymethyl cellulose is (0.6-4.5):1; and / or the weight ratio of the acrylic acid to the carboxymethyl cellulose is (0.05-0.35):
1.
3. The bare battery cell according to claim 2, characterized in that: According to the percentage by weight, In the material of the phase-change heat absorption layer, the polyethylene glycol accounts for 30-80%; and / or the acrylic acid accounts for 1-20%; and / or the carboxymethyl cellulose accounts for 10-50%.
4. The bare battery cell according to any one of claims 1 to 3, characterized in that: The material of the flame retardant layer includes polyethylene, polyamide and organic phosphorus flame retardant; Preferably, the oxygen content in the polyamide is ≥10wt%; Preferably, the organophosphorus flame retardant includes one or more of phosphates, phosphites and organophosphorus salts, more preferably, the phosphates include one or more of trichloroethyl phosphate, dimethyl methylphosphonate and triphenyl phosphate; more preferably, the phosphites include one or more of methyl phosphite, triethyl phosphite and tri(propylene glycol) phosphite; more preferably, the organophosphorus salts include one or more of aluminum phosphate, lanthanum phosphate and ammonium polyphosphate.
5. The bare battery cell according to claim 4, characterized in that: In the material of the flame retardant layer, the weight ratio of the polyethylene to the organic phosphorus flame retardant is (1-1.8):1; and / or the weight ratio of the polyamide to the organic phosphorus flame retardant is (0.5-0.9):
1.
6. The bare battery cell according to claim 4 or 5, characterized in that: In terms of weight percentage, the flame retardant layer comprises: The polyethylene accounts for 36-60%, preferably 40-45%; and / or, The polyamide accounts for 5 to 40%, preferably 18 to 25%; and / or, The organic phosphorus flame retardant accounts for 20 to 40%, preferably 30 to 40%.
7. The bare battery cell according to any one of claims 1 to 6, characterized in that: The thickness of the coating is 40 to 500 μm; Preferably, the thickness of the phase change heat absorption layer is 30-400 μm; and / or the thickness of the flame retardant layer is 10-100 μm.
8. A method for preparing a bare battery cell according to any one of claims 1 to 7, characterized in that: The bare cell comprises a surface negative electrode sheet, with the side of the shell facing the surface negative electrode sheet as the shell surface, and in the direction away from the shell surface, the surface negative electrode sheet comprises a coating, a current collector and a negative electrode film stacked in sequence; in the direction away from the shell surface, the coating comprises a flame retardant layer and a phase change heat absorption layer stacked in sequence; the current collector comprises a first surface and a second surface, and the preparation method comprises the following steps: Step S1, coating a phase change heat absorption layer raw material on the first surface of the current collector to obtain a phase change heat absorption layer; Step S2, coating the flame retardant layer raw material on the surface of the phase change heat absorption layer to obtain a flame retardant layer; Step S3, coating the raw material of the negative electrode film on the second surface of the current collector to obtain the surface negative electrode sheet; Step S4, using the surface negative electrode plate as the outermost electrode plate to prepare the bare battery cell.
9. The preparation method according to claim 8, characterized in that: The coating density of the phase change heat absorption layer raw material is 0.5-5 mg / cm 2 and / or, The coating density of the flame retardant layer material is 0.1-1.5 mg / cm 2 .
10. A secondary battery, characterized in that: A bare battery cell comprising any one of claims 1 to 7.